Evaluation of Prescribing Patterns and Guideline Based on the Therapy Management of Ischemic Stroke - Firdha Wardhani; Yunita Dyah Kusumaningrum (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Stroke management requires a comprehensive approach to ensure that treatment addresses both the acute event and underlying comorbidities and risk factors. Adherence to clinical guidelines is essential to optimize outcomes in ischemic stroke patients. This cross-sectional study was conducted from January 2021 to January 2022 using medical record data. Based on sample size calculation, a minimum of 97 patients was required, and data from 111 patients were included. The majority were female (54.1%) with a mean age of 62.11 years. None of the patients received fibrinolytic therapy, although it is recommended as the first-line treatment for eligible ischemic stroke cases. Instead, all patients received antiplatelet therapy, predominantly clopidogrel (52.3%). The most commonly prescribed antihypertensive agent was an angiotensin receptor blocker (52.2%), while atorvastatin (43.2%) was the most frequent lipid-lowering agent. Overall, most prescribed therapies were consistent with guideline recommendations, although individualised considerations, such as delayed presentation, contraindications, and comorbidities, likely influenced therapeutic decisions.